Rocket Observation of keV Electron Fluxes at Syowa Station - Matsumoto, Haruya; Kaya, Nobuyuki (1978)
P(論文) Electron fluxes in the energy range of 3-6keV during a quiet period were measured by a bared type electron spectrometer (ESM) on board the S-310JA-1 rocket at Syowa Station. Electron fluxes of ∿(10)^5 [(cm)^2・sec・ster・keV]^<-1> were observed in the height range between 90km and 210km. The ESM instrument proved to be usable in the future experiment. departmental bulletin paper